Implementasi Pendekatan Saintifik Guru Biologi SMA di Boyolali - Hariyatmi Hariyatmi; Denik Dwi Septiety; Ristiyani Wijayanti (Universitas Sebelas Maret, 2019)
The scientific approach is learning that adopts scientific steps in building knowledge through the scientific method. This study aims to determine the implementation of scientific biology teacher learning approaches in Boyolali in odd semester 2018/2019. The type of research used is descriptive. The sample in this study was one X grade teacher (N High School) and one XI teacher (Private High School). The sampling technique used in this study was purposive sampling. The research method uses an observation method to observe the teacher during learning for 3 meetings, assisted by video documentation during learning. Based on the research conducted, the results show that the implementation of high school Biology teacher scientific approach learning in Boyolali in the odd semester of 2018/2019 is sufficient (44.75%). Scientific learning used is Discovery Learning (40.95%) including adequate and Problem Based Learning (64%) including good. However, not all Biology teachers used the research using the two learning models. Biology teachers who have used both of these models are including good (64%) and who implement one learning model including the lack of categories (33.2%). Data were analyzed descriptively and based on the results of the study and discussion it can be concluded that the implementation of high school Biology teacher scientific learning in Boyolali odd semester 2018/2019 included enough (44.75%), with the learning model Discovery Learning and Problem Based Learning